Pilot Study of Salbutamol in the Treatment of Acute Asthma – Little Apparent Benefit to Dose and Frequency Adjustments. Issue 1 (3rd February 1997) - Sinclair, Douglas; MacKenzie, MG; Bowie, Dennis M
Abstract : STUDY OBJECTIVE: To compare two dosing regimens of salbutamol in acute asthma. DESIGN: Prospective randomized double-blind trial. SETTING: Urban emergency department. TYPE OF PARTICIPANTS: Patients who presented to the emergency department with moderate to severe asthma. INTERVENTIONS: All patients had pulmonary function testing and were randomized to group A (control; n=25) or group B (experimental; n=23). Group A (control) patients received salbutamol 2.5 mg delivered by wet aerosol at 0, 1 and 2 h (total dose 7.5 mg). At 20, 40, 80 and 100 mins a placebo aerosol was given. Group B patients received salbutamol 5 mg at 0 min and one-third the initial dose every 20 mins for a total of six doses by wet aerosol (total dose 15 mg). RESULTS: There were no differences in age, sex, preadmission medications or initial forced expiratory volume in 1 s (FEV1 ) between the groups. Forty-eight patients completed the study. Both groups of patients improved with mean absolute change in FEV1 of 700 mL in group A and 590 mL in group B. There were no statistical differences between the two groups in terms of treatment response, admission rates or side effects. CONCLUSIONS: This study of patients presenting with acute asthma demonstrated no differences in improvement during the initial 3 h of treatment with a standard dose of aerosolized salbutamol given at hourly intervals (total dose 7.5 mg) compared with a higher total dose given at 20 min intervals (total dose 15 mg).